Farming the Chaco: Tales from both sides of the fence - Jobbagy Gampel, Esteban Gabriel (2015)
The Chaco plains of Argentina, Bolivia and Paraguay host one the last large global reserves of fertile soils that are still uncultivated (Lambin et al., 2013). Most of this non farmed land is home for the most important tract of native dry forests of the world. Social, economic and technological changes are driving a fast expansion of agriculture over the whole region; challenging indigenous communities, rural settlers, farmers, conservationists, and policy makers alike (Grau et al., 2005). This special issue describes this process from multiple perspectives and explores its associated productive benefits and constrains as well as some of its major environmental impacts. Combining creative remote sensing approaches, field observations, and national statistics; a collective synthesis effort embodied in ten articles pushes available information and concepts a step further. While these contributions respond to an urgent regional demand, they provide at the same time useful knowledge for other active agricultural frontiers on dry regions like the Cerrados and Caatinga in Brazil and the Miombo and Mopane in Sub-Saharan Africa.